Local Scale Thermal Environment and Limited Gene Flow Indicates Vulnerability of Warm Edge Populations in a Habitat Forming Macroalga - Clark, Jennifer S.; Poore, Alistair G. B.; Coleman, Melinda A.; Doblin, Martina A. (Frontiers in Marine Science, 2020)
Species inhabiting warm-edge populations of their distribution are suggested to be at the forefront of global warming due to reduced fitness, limited gene flow and living close to their physiological thermal limits. Determining the scale that governs thermal niche and the functional responses of habitat-forming species to environmental stressors is critical for successful conservation efforts, particularly as coastal ecosystems are impacted by global change. Here, we examine the susceptibility of warm-edge populations to warming, in the habitat-forming macroalga, Hormosira banksii, from south-eastern Australia. We use a quantitative breeding design to quantify intraspecific variation in thermal performance (growth, ontogenic development and photosynthetic efficiency) of different genotypes sourced from sites at the equatorward distributional edge (warm-edge) and those towards the center of its distribution (non-edge). The genetic diversity and structure of H. banksii was also examined using microsatellite markers amongst the same sites. Our results found variable responses in thermal performance for growth and development. Warm-edge germlings grew optimally in lower temperatures tested and had narrower thermal breadth compared to non-edge germlings which grew in higher and more broader temperatures. Warm-edge germlings however, showed greater plasticity to tolerate high light indicated by a greater proportion of energy being dissipated as regulated nonphotochemical quenching (Y(NPQ)) than nonregulated nonphotochemical quenching (Y(NO)). Overall genetic diversity was lower at the warm-edge location with evidence of increased structuring and reduced gene flow in comparison to the non-edge location. Evidence of genetic structuring was not found locally between high and low shore within sites. Together, these data suggest that non-edge populations may be “thermally buffered” from increased temperatures associated with ocean warming. Warm-edge populations of H. banksii, however, may be vulnerable to warming, due to narrower thermal breadth and sensitivity to higher temperatures, with genetic impoverishment through loss of individuals likely to further reduce population viability.